The Effect of Product Price and Product Quality on Purchase Intention with Consumer Satisfaction as a Mediating Variable at Rumah Literasi Gorontalo - Syamsinah Syamsinah; Rahmatullah Lengato; Darman Darman (Eastasouth Institute, 2026)
This study aims to analyze the effect of product price and product quality on purchase intention with consumer satisfaction as a mediating variable among consumers of Rumah Literasi Gorontalo. This study is motivated by the importance of understanding the factors that influence consumer behavior in making purchases, particularly those related to price suitability, product quality, and the level of consumer satisfaction in shaping purchase intention. The research method used is a quantitative approach with an explanatory research design. The sampling technique used purposive sampling with the criterion that respondents were consumers who had purchased products at Rumah Literasi Gorontalo. Data were collected by distributing questionnaires using a Likert scale, and the data were then analyzed using the Structural Equation Modeling-Partial Least Square (SEM-PLS) method through the SmartPLS application. The results show that product price has a positive and significant effect on consumer satisfaction, with a T-Statistics value of 4,799 and a P-Values value of 0,000. Product quality also has a positive and significant effect on consumer satisfaction, with a T-Statistics value of 2,952 and a P-Values value of 0,003. In addition, product quality has a positive and significant effect on purchase intention, with a T-Statistics value of 2,852 and a P-Values value of 0,004. However, product price has no significant effect on purchase intention (T-Statistics 1,753; P-Values 0,080), and consumer satisfaction has no significant effect on purchase intention (T-Statistics 1,139; P-Values 0,255). The results of the indirect-effect test show that consumer satisfaction is unable to mediate the effect of product price or product quality on purchase intention. This study concludes that product quality is the factor that plays the strongest role in increasing the purchase intention of Rumah Literasi Gorontalo consumers, while consumer satisfaction has not been able to function as a mediating mechanism in this relationship. The results of this study provide practical implications for the management of Rumah Literasi Gorontalo to focus its strategy more on improving product quality and maintaining price suitability in accordance with the value received by consumers.